The Collapse of Middle Eastern Authoritarianism: breaking the barriers of fear and power - Salamey, Imad (2012)
This article analyses Middle Eastern authoritarianism and the contemporary political transformations which have swept the region. It suggests that, given the uneven spread of reform and the selectiveness of international intervention, the prioritisation of Middle Eastern stability over democratic transformation, combined with local authoritarian regimes' ability to use excessive force against their own populations and insurgents, are responsible for the persistence of the Middle East's post-cold war authoritarianism. The recent uprisings and reform movements can be explained from the perspective of historical grievance, based on social inequality and ethnic, sectarian, tribal or sectional disparities, as well as by advancements in communications technology and economic globalisation that have undermined long-standing national authoritarianism in favour of Middle Eastern civil rights and civil society movements. A global democratic consciousness has played a decisive role in providing ideological cohesiveness and (uneven) global political support to safeguard the collective action of the new civil rights movements. Recognising that democracy itself may have characteristic regional forms with greater and lesser tinges of recurrent authoritarianism, Middle Eastern democratic transformation hinges on the ability of these burgeoning movements to achieve a civic state and overcome authoritarian counter-resistance and international suspicion and fear.